(untitled) (Research, Society and Development, 2020)
Teas are rich in antioxidant compounds and many ready-to-drink teas are being developed with great acceptance in the market. However, the bioactive potential for these products should be preserved during the storage. The aim of this work was to evaluate changes in total phenolic content (TPC) and antioxidant capacity (AC) from six formulations of green and black ready-to-drink teas, stored in the dark or exposed to light during eight weeks at room temperature. The stability was evaluated every two weeks by measuring TPC by Folin-Ciocalteu and AC by ABTS and FRAP assays. In the absence of light TPC of green tea remained stable throughout the storage, but it dropped after two weeks when exposed to light. TPC for black tea decreased after four and two weeks, in the absence and presence of light, respectively. The AC for green tea decreased after two weeks, in the presence of light, however the decay was greater for the FRAP assay. In the absence of light, changes in AC for black tea were observed only for samples assayed by FRAP after two weeks. A reduction in the AC (FRAP and ABTS) occurred after four weeks for both samples exposed to light. The results show that to retain the majority of their TPC and AC these tea drinks should be commercialized in opaque packages and stored for up to eight weeks.